Development of Infrastructure And Economic Growth of Papua Province - Siti Munawaroh; Tri Haryanto (MediaTrend, 2021)
Efforts are being make equitable development through accelerated infrastructure development by providing quality infrastructure facilities and services. The government continues encourage the development of damaged infrastructure in order to increase economic growth, especially areas do not have good access. The purpose this study is determine the effect of infrastructure development on economic growth Papua Province. This study uses panel data regression with the Random Effect Model. Infrastructure data used this study are road infrastructure, educational infrastructure, health infrastructure from 29 districts / cities period 2011-2018. The results is road infrastructure and educational infrastructure have a positive and significant influence economic growth, while health infrastructure have a positive but not significant effect economic growth Papua Province. The regional government must be increase the quantity and quality of teaching staff, services and health facilities at regions isolated.